2019
DOI: 10.1371/journal.pone.0211205
|View full text |Cite
|
Sign up to set email alerts
|

Improving socioeconomic status may reduce the burden of malaria in sub Saharan Africa: A systematic review and meta-analysis

Abstract: BackgroundA clear understanding of the effects of housing structure, education, occupation, income, and wealth on malaria can help to better design socioeconomic interventions to control the disease. This literature review summarizes the relationship of housing structure, educational level, occupation, income, and wealth with the epidemiology of malaria in sub-Saharan Africa (SSA).MethodsA systematic review and meta-analysis was conducted following the preferred reporting items for systematic reviews and meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
89
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 122 publications
8
89
3
2
Order By: Relevance
“…Furthermore, our data suggest that children with educated mothers had less odds of malaria. As mother's education is often used as a proxy for household wealth (23), previous studies have found a reduced risk of malaria in wealthier households (24). There is the consistent trend in association between the household wealth index, an indicator related to other household determinants that impact on malaria incidence, with the poor suffering the brunt of malaria cases and perhaps mortality.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, our data suggest that children with educated mothers had less odds of malaria. As mother's education is often used as a proxy for household wealth (23), previous studies have found a reduced risk of malaria in wealthier households (24). There is the consistent trend in association between the household wealth index, an indicator related to other household determinants that impact on malaria incidence, with the poor suffering the brunt of malaria cases and perhaps mortality.…”
Section: Discussionmentioning
confidence: 90%
“…Malaria is a major public health problem in developing economies, especially in sub-Sahara Africa (SSA) where it is responsible for substantial morbidity and mortality (1) as well as other socioeconomic losses (2). The disease is caused by Plasmodium parasite, and transmitted through the bite of infected female Anopheles mosquitoes (3).…”
Section: Introductionmentioning
confidence: 99%
“…Continuous interest must be maintained, as they affect mainly poor, or neglected, people in the world, and are responsible for a high level of mortality in these populations and put at risk many countries, including developed ones. (1,6,175,176) The intensification and the ease of people's migration are modifying the spread of many diseases, including those ones. Even considering the higher financial support for malaria and tuberculosis than for other diseases that are considered neglected, the amount invested is still lower than the estimated need.…”
Section: Discussionmentioning
confidence: 99%
“…The dramatic increase of parasite resistance to routinely used chemotherapeutics and the absence of vaccines aggravate the situation dramatically. [35][36][37] For this reason, several research groups from medicinal chemistry, pharmacy, and infection biology focus on the search of new effective agents for the treatment of tropical infectious diseases. In the recent years, intense phytochemical studies on African plants have led to the discovery of terpenoids, alkaloids, avonoids, quinones, lignans, coumarins, and many other natural products displaying excellent antiprotozoal activities, [38][39][40][41][42][43][44][45] thus providing templates and new scaffolds for the development of a new generation of more potent drugs.…”
Section: View Article Onlinementioning
confidence: 99%